Nyandhing Method in Dance Learning at the Umah Seni Kuwung Wetan Banyuwangi Dance Studio - puput, puput; Yanuartuti, Setyo (Solah, 2025)
Umah Seni Kuwung Wetan Banyuwangi dance studio has an interesting method for learning dance. This method is called a method side by side This method can only be found in Kuwung Wetan because it was obtained by Dwi Agus Cahyono as the founder of the studio which was then applied when establishing the Dance Studio. Researchers are interested in examining the nyandhing method used by this studio because it is a superior method that is not found in other studios. The formulation of this research problem is (1) what is the background to the establishment of the Umah Seni Kuwung Wetan Banyuwangi Dance Studio, (2) how to apply the method side by side in learning dance, (3) what are the obstacles faced in learning dance at the Umah Seni Kuwung Wetan Banyuwangi Dance Studio. The objectives of this research are (1) to describe the background to the founding of the Dance Studio Umm Banyuwangi Kuwung Wetan Art, (2) describes the application of the method side by side in dance learning at the Dance Studio Umm Seni Kuwung Wetan Banyuwangi, (3) describes the obstacles faced in learning dance at the Dance Studio Umm East Kuwung Art of Banyuwangi. The research approach uses descriptive qualitative data collection methods using observation, interviews and documentation. Data analysis techniques are carried out by data reduction, data presentation, and confirmation of conclusions. The research results show that this studio was founded with the aim of providing interesting dance and music training to suit the characteristics of Banyuwangian Dance learning. Method side by side in his learning This is done using steps such as physical exercise, basic dance movement exercises, movement exercises followed by counting, and movement exercises with take the drum in accordance drum the dance. This is done to make it easier for students to match movements with rhythm drum his. The obstacles faced come from internal factors (management, coaches, dancers, musicians) and external factors (society, environment, government). Keywords: Nyandhing Method, Dance Learning, Umah Seni Kuwung Wetan Banyuwangi Dance Studio.